Integrated Control of some Agricultural Production using Satellite Remote Sensing in Cyprus - Hadjimitsis, Diofantos G.; Clayton, C.R.I.; Themistocleous, Kyriacos; Papadopoulos, Periklis (My University, 2004)
This project attempts to evaluate the suitability of the remote sensing techniques to monitoring the integrity of farmers’ declarations. The objective of this study is to develop a remote sensing technique in which land-use acreage estimation and timely assessment of crop production are achieved. The underlying principle for the acreage estimation is the comparison between the estimates found using ground surveys and supervised and unsupervised classification. Indeed, linear regression or equivalent statistical analysis can be used to measure the correlation of both estimates. Crop Monitoring for some specific fields can be achieved using both ground and satellite remotely sensed data.
Keywords: Satellite Remote sensing; Cyprus; Agricultural Production